2006
DOI: 10.1038/sj.ijir.3901435
|View full text |Cite|
|
Sign up to set email alerts
|

The prevalence of erectile dysfunction in men visiting outpatient clinics

Abstract: The prevalence of erectile dysfunction (ED) in men visiting outpatient clinics was analyzed using data reported by 1352 randomly chosen physicians who were requested to interview five to 20 consecutive patients aged X40 years about the presence of ED. A total of 25.12% of the physicians returned the questionnaires, containing data on 3552 patients, of whom 42.7% had ED, 44.9% had no ED and 12.4% declined to answer the questions. The duration of ED was o1 year in 8.1% of patients, 1-2 years in 32.2% and 42 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…Using an erectile rigidity VAS, the mean rigidity was 43 (22, 39-47, 0-80)%. In all, 90% of patients had IIEF EFD scores available; the mean score at presentation was 15 (4,(13)(14)(15)(16)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) 16). Cavernosograms taken in the six patients with vasculogenic ED showed crural venous leak in five.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an erectile rigidity VAS, the mean rigidity was 43 (22, 39-47, 0-80)%. In all, 90% of patients had IIEF EFD scores available; the mean score at presentation was 15 (4,(13)(14)(15)(16)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) 16). Cavernosograms taken in the six patients with vasculogenic ED showed crural venous leak in five.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study there was a prolonged delay from the onset of ED to comprehensive evaluation and treatment (mean 22.6 months), regardless of the cause of ED (psychogenic or vasculogenic). A delay in seeking treatment is also common among older men; at presentation, < 10% have ED of < 1 year in duration, a third has ED lasting 1-2 years and most seek treatment after > 2 years of ED [10]. Heruti et al [11] showed that even after sexual dysfunction is diagnosed only a minority of young men seek evaluation and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide it is estimated that over 100,000,000 men are affected [1]. It is expected that between 1995 and 2025 the prevalence of ED worldwide will have increased by more than 110% [2].…”
Section: Epidemiologymentioning
confidence: 99%
“…Erectile dysfunction (ED) is a major men’s health issue affecting 30 million men in the United States alone and this number is expected to increase two-fold in the next 20 years with the aging population (Haczynski et al, 2006). Normal erectile function requires that a number of different cell types and systems work in concert.…”
Section: Introductionmentioning
confidence: 99%